Modeling economic growth in contemporary Slovakia - Augustín, Michael; Jančovič, Peter; Sergi, Bruno S. (Bingley, U.K. : Emerald Publishing Limited, 2024)
Following the peaceful dissolution of Czechoslovakia, the Slovak Republic emerged as an independent nation and embarked on a journey of economic transition and reform. During the thirty early years of independence, Slovakia faced many challenges, including establishing new economic policies, institutions, and legal frameworks. Modeling Economic Growth in Contemporary Slovakia analyses various aspects of Slovakia's economy, including recent developments and events such as the COVID-19 pandemic and war in Ukraine. The chapters also highlight issues that arise from the current economic model, making it difficult for Slovakia to revitalize and adapt the economy to new circumstances. This volume is a must-read for professionals and academics who wish to comprehend the basis of Slovakia's growth and forecast its viability in the coming years. Entrepreneurship and Global Economic Growth presents modern examinations of economic growth at national, regional, and global levels. Each book in this series discusses different dimensions of the changing economic and industrial contexts and examines in detail their impact on the nature of growth and development.
Introduction. Michael augustín, peter jancovic, and bruno s. Sergi -- Part I. Dynamics of the Slovak economy -- Chapter 1. Historical development of the czechoslovak and Slovak economies in the transition period / Juraj Sipko -- Chapter 2. Slovak experience with capitalism: The myth of the tatra tiger / Michael Augustín and Peter Daubner -- Chapter 3. Slovakias changing position among economies of the European Union and the world / Natália Zagoršeková -- Chapter 4. Critical perspectives to growth-based approach as policy goal and dominant measure of policy performance in Slovakia / Jakub Csabay -- Part II. Policies, institutions, and markets -- Chapter 5. Empirical study of the Slovak labor market in the breakthrough development period / Renáta Pitonáková and Ladislav Kabát -- Chapter 6. The residential real estate market in the Slovak republic / Eva Horvátová -- Chapter 7. External economic relations of the Slovak republic: Trade, investment and related policies / Peter Jancovic -- Chapter 8. Divergence of Slovak regions: Bumpy road to decentralization / Anton Marcincin -- Chapter 9. The political-economic foundations of Slovakia's dependent growth model / Jakub Szabó -- Part III. Characteristics and performance of selected industries -- Chapter 10. Slovakia as an automobile superpower or factory economy? / Monika Martišková and Katarína Lukácová -- Chapter 11. Slovak innovation ecosystem: It & digital innovations / Jaroslav Vokoun -- Chapter 12. Business service centers: A new growth impulse for the Slovak economy / Tomáš Dudáš -- Chapter 13. Culture and tourism: Hidden potential for Slovak economy / Kristína Baculáková -- Chapter 14. Economic trajectories of Slovakia and czechia: Twins or unique cases? / Lubor Lacina and Dunja Spasojevic.
Includes bibliographical references and index.
Print version record.
Keywords: Economic development -- Solvakia; Business & Economics -- Development -- Economic Development; Development economics and emerging economies; Slovakia -- Economic conditions -- 21st century